The Potential Role of RT-LAMP in SARS-CoV-2 Diagnosis Based on Limit of Detection - Celebi, Ayse (Open Schools Journal for Open Science, 2022)
The COVID-19 pandemic, caused by the novel coronavirus SARS-CoV-2, that arose in 2019 underscored the significance of testing and diagnostics in order to combat the rapid spread of the disease. The most common method for SARS-CoV-2 RNA detection has been the RT-qPCR method, which is insufficient in terms of meeting the immense demand for testing due to its relatively high time-consumption. Under these circumstances, the urgent need for a rapid and similarly sensitive testing arised, and the RT-LAMP method was proven to be a promising alternative. This review compares the lowest concentration levels of SARS-CoV-2 RNA that these two mentioned methods can detect, examining several reviews and research. It was found that the detection limit of RT-qPCR is lower in comparison to RT-LAMP, which demonstrates a higher sensitivity, thus, reducing the false negative outcomes. Nonetheless, RT-LAMP is more convenient for being deployed as a point-of-care test for vast amounts of people considering its rapidity in detection and simplicity, albeit it has a higher detection limit compared to RT-qPCR.